Ionizing radiation protection clothing

By using a combination of polyvinyl matrix with functional materials and modified glass fibers, the ionizing radiation-resistant garments made to solve the weight and toxicity of existing lead-based materials, achieving stronger shielding and flame retardant properties.

CN119736726APending Publication Date: 2025-04-01ANHUI YINGLIU JIUYUAN NUCLEAR ENERGY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510041540.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing anti-ionizing radiation composite materials use lead or lead compounds, which have problems such as large weight, narrow shielding range and toxicity, making it difficult to meet higher shielding needs.

Method used

Polyethylene is used as the matrix, combined with functional shielding material and modified glass fiber, and non-woven fabric is made by melt spinning and needle-punching, and finally cut and sew into ionizing radiation-proof clothing.

Benefits of technology

It improves the shielding ability of clothing to neutrons and gamma rays, enhances mechanical properties and breathability, reduces load weight, and significantly improves flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237116200000041
    Figure BDA0005237116200000041
  • Figure BDA0005237116200000042
    Figure BDA0005237116200000042
  • Figure BDA0005237116200000051
    Figure BDA0005237116200000051
Patent Text Reader

Abstract

The invention discloses an anti-ionizing radiation clothing, belonging to the technical field of ionizing radiation shielding materials. It comprises the following raw materials by weight: 70-80 parts of polyethylene resin, 30-40 parts of functional shielding materials, 14-20 parts of modified glass fibers, 6-18 parts of synergistic flame retardants, 0.5-1.5 parts of initiators, and 4-6 parts of processing aids. The invention prepares non-woven fabrics by a needle punching method after melt spinning of high molecular weight polyethylene and other functional materials, and finally prepares clothing; polyethylene is used as a matrix to give clothing a shielding effect on neutrons; wherein the functional shielding material further improves the shielding ability; the non-woven fabrics are prepared by a needle punching method, which improves the air permeability and comfort of the clothing; wherein the modified glass fibers can greatly enhance the mechanical properties of the clothing; the prepared synergistic flame retardant can significantly improve the flame retardant performance of the clothing, and the performance is long-term and stable; it has important application value in the technical field of ionizing radiation shielding materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ionizing radiation shielding materials, and in particular relates to an ionizing radiation protection garment. Background Art

[0002] With the increasing demand for energy and the emphasis on the environment, new energy sources are developing rapidly. Nuclear energy, as a clean and efficient form of energy, has received widespread attention. However, while using nuclear energy, nuclear reactors will produce extremely radioactive rays, called nuclear radiation. Nuclear radiation is the microscopic particle flow released during the transformation of atomic nuclei from one structure or one energy state to another structure or another energy state. It poses a great threat to people's life, health and property safety. Nuclear radiation can cause ionization or excitation of matter and is a type of ionizing radiation.

[0003] Ionizing radiation refers to radiation that carries enough energy to free electrons in atoms or molecules of matter, thereby ionizing these atoms or molecules. The characteristics of ionizing radiation are short wavelength, high frequency and high energy. Ionizing radiation can release (ionize) one or more electrons from atoms, molecules or other bound states. Ionizing radiation is a general term for all radiation that can cause ionization of matter. There are many types of radiation. High-speed charged particles include alpha particles, beta particles, and protons. Uncharged particles include neutrons, X-rays, and gamma rays.

[0004] With the increasing application of various ionizing radiations in industrial society, the requirements for the protection and health of relevant staff are also getting higher and higher. At present, the anti-ionizing radiation composite materials used in China have always been limited to using lead or lead compounds as the main additives to prevent the harm of ionizing radiation to the human body. They are mainly used for protection of x-rays, gamma rays, alpha surface contamination, beta surface contamination, and hospital radiation equipment room staff, non-destructive testing protection, nuclear protection, etc., but such products have a large specific gravity and a narrow shielding range, and lead itself is toxic, which is easy to cause physical harm to relevant users and also pollute the environment. Due to the serious harm caused by lead to the human body and the environment, countries such as Europe and the United States have restricted the use of lead-containing products in their own countries. Therefore, for wearable shielding materials, shielding materials made of polymers as the matrix are increasingly attracting people's attention. However, polyethylene itself has poor flame retardancy and mechanical properties, and poor compatibility with reinforcing materials such as glass beads and glass fibers. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of ionizing radiation shielding material technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide an ionizing radiation protection garment.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] An ionizing radiation protection garment is prepared by the following steps:

[0008] The polyethylene resin, functional shielding material and modified glass fiber are dried in an oven at 80-100°C, added to a high-speed mixer with a synergistic flame retardant, an initiator and a processing aid, and then added to a twin-screw extruder for melt spinning to obtain a staple fiber material. The staple fiber material is opened, and then laid on a net after rough combing and combing. Pre-needling and main needling are performed with triangular needles, and then the edges are trimmed after three roller pressing to obtain a non-woven fabric. Finally, the non-woven fabric is cut and sewn to obtain anti-ionizing radiation clothing.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 70-80 parts of polyethylene resin, 30-40 parts of functional shielding material, 14-20 parts of modified glass fiber, 6-18 parts of synergistic flame retardant, 0.5-1.5 parts of initiator, and 4-6 parts of processing aid.

[0010] Furthermore, the functional shielding material is one or more of boron nitride, boron carbide, boric acid, tantalum powder and tungsten powder.

[0011] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.

[0012] Furthermore, the processing aid is one of paraffin and zinc stearate.

[0013] With polyethylene as the matrix, the elastic scattering of C and H elements in polyethylene can slow down neutrons, giving the material a shielding effect on neutrons; the added functional shielding material has good shielding capabilities for thermal neutrons, fast neutrons, and high-energy neutrons, and can also effectively shield gamma rays; the non-woven fabric is made by needle punching, which improves the breathability and comfort of the wearable shielding suit, reduces the load weight of the staff, and has a better shielding effect.

[0014] Furthermore, the modified glass fiber is prepared by the following steps:

[0015] After soaking the chopped glass fiber in acetone for 12 hours, take it out, wash it with distilled water for 4-5 times, dry it in an oven, add it to an ethanol-water solution, and then add silane coupling agent KH-570. Control the temperature to 85°C and keep the reaction for 5 hours with continuous stirring. After the reaction is completed, filter it, wash it with anhydrous ethanol, and vacuum dry it for 2 hours to obtain modified glass fiber.

[0016] Further, the ratio of glass fiber, acetone, ethanol aqueous solution, and silane coupling agent KH-570 is 1 g:100 mL:100 mL:5.2 g;

[0017] Chopped glass fiber is an excellent reinforcement material with good mechanical properties. The chopped glass fiber is modified with silane coupling agent KH-570, and unsaturated carbon-carbon double bonds are introduced on the surface of the chopped glass fiber, that is, an organic layer is formed on its surface, which can improve the hydrophobicity of the surface of the chopped glass fiber, thereby enhancing the compatibility of the chopped glass fiber with the polyethylene matrix, so that the performance of the chopped glass fiber can be fully utilized, and the mechanical properties of the polyethylene matrix are greatly enhanced.

[0018] Furthermore, the synergistic flame retardant is prepared by the following steps:

[0019] S1. Add pentaerythritol and trichlorothiophosphorus to a four-necked flask equipped with a thermometer and a reflux condenser, stir evenly, heat in an oil bath, set the temperature to 145°C, reflux for 6 hours, until no hydrogen chloride gas is released, then raise the temperature to 165°C, heat for another 1.5 hours, and the reaction is complete. After the device is cooled to room temperature, extract with boiling water for 4 times, remove the sticky substance at the bottom of the bottle by decantation, concentrate to remove part of the water, cool and crystallize, filter, and dry to obtain intermediate 1; the ratio of pentaerythritol to trichlorothiophosphorus is 16.7g:14.8g;

[0020] Pentaerythritol undergoes a nucleophilic substitution reaction with phosphorus trichloride to obtain intermediate 1; the structure of intermediate 1 is shown below:

[0021]

[0022] S2, in a three-necked flask equipped with a stirring device, the air in the nitrogen exhaust device is introduced, and then intermediate 1, adipoyl chloride and N, N-dimethylformamide are added, and after stirring and mixing, 4-dimethylaminopyridine (DMAP, catalyst) and triethylamine (acid binding agent) are added, and after stirring and mixing again, the reaction temperature is controlled to 60 ° C, and the stirring reaction is 6h. After the reaction is completed, the reaction is filtered, and the solvent is removed by distillation under reduced pressure, washed with deionized water, and vacuum dried to obtain intermediate 2; the ratio of the amount of intermediate 1, adipoyl chloride, N, N-dimethylformamide, 4-dimethylaminopyridine, and triethylamine is 19.6g:19.4g:100mL:0.2g:15mL;

[0023] 4-Dimethylaminopyridine is used as a catalyst, triethylamine removes the hydrogen chloride generated by the reaction, accelerates the reaction, and the acyl chloride on the adipoyl chloride and the hydroxyl group on the intermediate 1 undergo an acylation reaction. By controlling the molar ratio of the two to be close to 1:1 and the adipoyl chloride is slightly excessive, only one acyl chloride on the adipoyl chloride participates in the reaction to obtain the intermediate 2. The specific reaction process is shown below:

[0024]

[0025] S3. At room temperature, under nitrogen protection, 2-vinyl-4,6-diamino-1,3,5-triazine, triethylamine (acid binding agent) and N,N-dimethylformamide were mixed in a three-necked flask equipped with a stirring device, stirred until the solid was completely dissolved, and then intermediate 2 was added, and the reaction was stirred in a warm water bath at 55°C for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 4:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain a synergistic flame retardant; the ratio of the amount of 2-vinyl-4,6-diamino-1,3,5-triazine, triethylamine, N,N-dimethylformamide, and intermediate 2 was 13.7g:30mL:150mL:69.1g;

[0026] 2-vinyl-4,6-diamino-1,3,5-triazine and intermediate 2 undergo amidation reaction, and a synergistic flame retardant is obtained by controlling the molar ratio of the two to be close to 1:2 and the intermediate 2 to be slightly excessive; the specific reaction process is as follows:

[0027]

[0028] The prepared synergistic flame retardant molecule contains triazine, caged phosphonate, sulfur element and carbon-carbon double bond structure. Among them, the introduced triazine structure is a nitrogen-based flame retardant. When burned, it will produce nitrogen-containing gas, dilute and reduce the smoke density, and self-condense at high temperature to form melem to make the carbon layer tight, thereby improving the flame retardant performance of the matrix; in addition, the molecule contains two sulfur-containing caged phosphonate structures. Caged phosphonate is a phosphorus-based flame retardant. Caged phosphonate decomposes at high temperature to produce phosphoric acid, metaphosphoric acid, polymetaphosphoric acid and other substances. These substances have strong dehydration properties and can dehydrate and carbonize the polymer surface, forming a carbonized layer. It not only reduces the heat conduction from the flame to the condensed phase, but also prevents the generation of flammable gases, and has better stability than traditional phosphorus-based flame retardants. Moreover, sulfur atoms can release non-flammable gases such as sulfur dioxide during the combustion process. These gases can dilute the concentration of flammable gases and oxygen, and can synergize with the phosphorus element in the caged phosphonate and the nitrogen element in the triazine to promote the dehydration of the substrate into carbon, enhance the flame retardant effect of the condensed phase, and significantly enhance the flame retardant properties of the matrix; finally, the carbon-carbon double bonds in the synergistic flame retardant molecules can produce chemical bonds with the polyethylene matrix to improve the stability of the synergistic flame retardant.

[0029] Beneficial effects of the present invention:

[0030] The invention manufactures the non-woven fabric by melt-spinning the high molecular weight polyethylene and other functional materials, and then manufactures the clothing by needle punching.

[0031] 1. Polyethylene is used as the matrix, which gives the clothing a shielding effect against neutrons;

[0032] 2. The added functional shielding materials further improve the shielding ability against neutrons and also enhance the shielding ability of clothing against gamma rays;

[0033] 3. The non-woven fabric is made by needle punching, which improves the breathability and comfort of the clothing and reduces the load weight of the staff;

[0034] 4. By modifying the chopped glass fiber, it has better compatibility with polyethylene than ordinary glass fiber, which can greatly enhance the mechanical properties of clothing;

[0035] 5. The various groups in the prepared synergistic flame retardant molecules can play a synergistic role, significantly improving the flame retardant properties of clothing, and the performance is long-lasting and stable;

[0036] Therefore, the clothing prepared by the present invention has good mechanical properties, strong shielding ability, good air permeability, good comfort, and stable and efficient flame retardancy, and has important application value in the technical field of ionizing radiation shielding materials. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1

[0039] Preparation of synergistic flame retardants:

[0040] S1. In a four-necked flask equipped with a thermometer and a reflux condenser, add 16.7 g of pentaerythritol and 14.8 g of trichlorothiophosphorus, stir evenly, heat in an oil bath, set the temperature to 145°C, reflux for 6 h, until no hydrogen chloride gas is released, then raise the temperature to 165°C, heat for another 1.5 h, and the reaction is complete. After the device is cooled to room temperature, extract with boiling water 4 times, remove the sticky substance at the bottom of the bottle by decantation, concentrate to remove part of the water, cool and crystallize, filter, and dry to obtain intermediate 1;

[0041] S2. In a three-necked flask equipped with a stirring device, nitrogen was introduced into the air in the device, and then 19.6 g of intermediate 1, 19.4 g of adipoyl chloride and 100 mL of N,N-dimethylformamide were added, and after stirring and mixing, 0.2 g of 4-dimethylaminopyridine and 15 mL of triethylamine were added. After stirring and mixing again, the reaction temperature was controlled to 60 ° C. The reaction was stirred for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was removed by distillation under reduced pressure, the mixture was washed with deionized water, and vacuum dried to obtain intermediate 2;

[0042] S3. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 13.7 g of 2-vinyl-4,6-diamino-1,3,5-triazine, 30 mL of triethylamine and 150 mL of N,N-dimethylformamide were mixed and stirred until the solid was completely dissolved. Then, 69.1 g of intermediate 2 was added and stirred in a 55°C warm water bath for 6 h. After the reaction was completed, the mixture was filtered and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1). The eluent was removed by rotary evaporation and dried in vacuo to obtain a synergistic flame retardant.

[0043] Embodiment 2

[0044] Preparation of synergistic flame retardants:

[0045] S1. In a four-necked flask equipped with a thermometer and a reflux condenser, add 33.4 g of pentaerythritol and 29.6 g of trichlorothiophosphorus, stir evenly, heat in an oil bath, set the temperature to 145°C, reflux for 6 h, until no hydrogen chloride gas is released, then raise the temperature to 165°C, heat for another 1.5 h, and the reaction is complete. After the device is cooled to room temperature, extract with boiling water 4 times, remove the sticky substance at the bottom of the bottle by decantation, concentrate to remove part of the water, cool and crystallize, filter with suction, and dry to obtain intermediate 1;

[0046] S2. In a three-necked flask equipped with a stirring device, nitrogen was introduced into the air in the device, and then 39.2 g of intermediate 1, 38.8 g of adipoyl chloride and 200 mL of N, N-dimethylformamide were added, and after stirring and mixing, 0.4 g of 4-dimethylaminopyridine and 30 mL of triethylamine were added. After stirring and mixing again, the reaction temperature was controlled to 60 ° C. The reaction was stirred for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was removed by distillation under reduced pressure, the mixture was washed with deionized water, and vacuum dried to obtain intermediate 2;

[0047] S3. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 27.4 g of 2-vinyl-4,6-diamino-1,3,5-triazine, 60 mL of triethylamine and 300 mL of N,N-dimethylformamide were mixed and stirred until the solid was completely dissolved. Then, 138.2 g of intermediate 2 was added and stirred in a warm water bath at 55°C for 6 h. After the reaction was completed, the mixture was filtered and part of the solvent was first removed by rotary evaporation. Then, the mixture was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), the eluent was removed by rotary evaporation, and the mixture was dried in vacuo to obtain a synergistic flame retardant.

[0048] Embodiment 3

[0049] Preparation of modified glass fiber:

[0050] Soak 1g of chopped glass fiber in 100mL of acetone for 12h, take it out, wash it with distilled water for 4-5 times, dry it in an oven, add it to 100mL of ethanol aqueous solution, add 5.2g of silane coupling agent KH-570, control the temperature to 85℃, keep the reaction for 5h, stir continuously during the reaction, filter it, wash it with anhydrous ethanol, and vacuum dry it for 2h to obtain modified glass fiber.

[0051] Embodiment 4

[0052] 70 g of polyethylene resin, 30 g of boron nitride and 14 g of modified glass fiber prepared in Example 3 were dried in an oven at 80° C., and then added to a high-speed mixer and mixed with 6 g of the synergistic flame retardant prepared in Example 1, 0.5 g of benzoyl peroxide and 4 g of paraffin. After mixing, the mixture was added to a twin-screw extruder, melt-blended and extruded to obtain a polyethylene shielding material.

[0053] Embodiment 5

[0054] 75 g of polyethylene resin, 35 g of boron carbide and 17 g of modified glass fiber prepared in Example 3 were dried in an oven at 90° C., and then added to a high-speed mixer for mixing with 12 g of the synergistic flame retardant prepared in Example 2, 1 g of lauroyl peroxide and 5 g of zinc stearate. After mixing, the mixture was added to a twin-screw extruder for melt blending and extrusion to obtain a polyethylene shielding material.

[0055] Embodiment 6

[0056] 80 g of polyethylene resin, 40 g of boron carbide and 20 g of the modified glass fiber prepared in Example 3 were dried in an oven at 100° C., and then added to a high-speed mixer for mixing with 18 g of the synergistic flame retardant prepared in Example 2, 1.5 g of lauroyl peroxide and 6 g of zinc stearate. After mixing, the mixture was added to a twin-screw extruder for melt blending and extrusion to obtain a polyethylene shielding material.

[0057] Embodiment 7

[0058] 80g of polyethylene resin, 40g of boron carbide and 20g of the modified glass fiber prepared in Example 3 were dried in an oven at 100°C, and then added to a high-speed mixer for mixing with 18g of the synergistic flame retardant prepared in Example 2, 1.5g of lauroyl peroxide and 6g of zinc stearate. After mixing, the mixture was added to a twin-screw extruder for melt spinning to obtain a staple fiber material. The staple fiber material was opened, and then laid after rough combing and combing. Pre-needling and main needling were performed with triangular needles, and then the edges were trimmed after three roller pressing to obtain a non-woven fabric. Finally, the non-woven fabric was cut and sewn to obtain an anti-ionizing radiation clothing.

[0059] Comparative Example 1

[0060] The synergistic flame retardant in Example 6 was replaced by a commercially available phosphorus-based flame retardant of equal quality, and the remaining steps were the same as those in Example 6.

[0061] Comparative Example 2

[0062] Commercially available polyethylene shielding material was used.

[0063] Embodiments 4, 5, 6, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0064] The tensile strength is determined using the national standard GB / T 1040.2-2022 "Determination of tensile properties of plastics";

[0065] The oxygen index was determined using the national standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method"; after leaving Examples 4, 5, 6 and Comparative Example 1 at room temperature for 100 days, the limiting oxygen index was determined again;

[0066] The Cf-252 neutron radiation source was used and the 3He counter was used to measure the fast neutron attenuation coefficient.

[0067] Using 60CoY radiation source and NaI crystal detector, the γ radiation attenuation coefficient of the sample was measured;

[0068] The measured results are shown in the following table:

[0069]

[0070]

[0071] It can be seen from the above table that the polyethylene shielding material prepared in the embodiments of the present invention has strong shielding ability and good mechanical properties. In embodiments 4 to 6, with the increase of the content of the synergistic flame retardant, the flame retardant properties are greatly improved, the effect on the mechanical properties is small, and the flame retardant properties are stronger than the control group, the performance is long-term and stable, and it has important application value in the field of ionizing radiation shielding material technology.

[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0073] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An ionizing radiation protection garment, characterized in that: Prepared by the following steps: The polyethylene resin, functional shielding material and modified glass fiber are dried in an oven, added to a high-speed mixer with a synergistic flame retardant, an initiator and a processing aid, and then added to a twin-screw extruder for melt spinning to obtain a staple fiber material. The staple fiber material is opened, and then laid on a net after rough combing and combing. Pre-needling and main needling are performed with triangular needles, and then the edges are trimmed after three roller pressing to obtain a non-woven fabric. Finally, the non-woven fabric is cut and sewn to obtain anti-ionizing radiation clothing.

2. The ionizing radiation protection clothing according to claim 1, characterized in that: The synergistic flame retardant is prepared by the following steps: S1. Add pentaerythritol and phosphorus thiochloride into a four-necked bottle, stir evenly, heat in an oil bath, reflux at 145°C for 6 hours, until no hydrogen chloride gas is released, then raise the temperature to 165°C, heat for another 1.5 hours, and complete the reaction. Cool, extract with boiling water, remove the sticky substance at the bottom of the bottle by decantation, concentrate to remove part of the water, cool and crystallize, filter with suction, and dry to obtain intermediate 1; S2. Nitrogen was introduced into a three-necked flask, and intermediate 1, adipoyl chloride and N,N-dimethylformamide were added, and after stirring and mixing, 4-dimethylaminopyridine and triethylamine were added, and after stirring and mixing again, the mixture was stirred at 60° C. for 6 h. After the reaction was completed, the mixture was filtered, distilled under reduced pressure, washed, and dried in vacuo to obtain intermediate 2; S3. At room temperature, 2-vinyl-4,6-diamino-1,3,5-triazine, triethylamine and N,N-dimethylformamide were mixed under nitrogen protection, and the mixture was stirred until the solid was completely dissolved. Then, intermediate 2 was added, and the mixture was stirred in a 55°C warm water bath for 6 hours. After the reaction was completed, the mixture was filtered, rotary evaporated, purified by column chromatography, rotary evaporated, and vacuum dried to obtain a synergistic flame retardant.

3. The ionizing radiation protection clothing according to claim 2, characterized in that: In step S1, the ratio of pentaerythritol to phosphorus thiochloride is 16.7 g:14.8 g.

4. The ionizing radiation protection clothing according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, adipoyl chloride, N,N-dimethylformamide, 4-dimethylaminopyridine and triethylamine is 19.6 g:19.4 g:100 mL:0.2 g:15 mL.

5. The ionizing radiation protection clothing according to claim 2, characterized in that: In step S3, the ratio of the amount of 2-vinyl-4,6-diamino-1,3,5-triazine, triethylamine, N,N-dimethylformamide, and intermediate 2 is 13.7 g:30 mL:150 mL:69.1 g.

6. The ionizing radiation protection clothing according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 70-80 parts of polyethylene resin, 30-40 parts of functional shielding material, 14-20 parts of modified glass fiber, 6-18 parts of synergistic flame retardant, 0.5-1.5 parts of initiator, and 4-6 parts of processing aid.

7. The ionizing radiation protection clothing according to claim 1, characterized in that: The functional shielding material is one or more of boron nitride, boron carbide, boric acid, tantalum powder and tungsten powder.

8. The ionizing radiation protection clothing according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: The chopped glass fibers were soaked in acetone for 12 hours, taken out, washed, dried, added to an ethanol aqueous solution, and then added with silane coupling agent KH-570. The temperature was controlled at 85°C and the reaction was kept warm for 5 hours with continuous stirring. After the reaction was completed, the fibers were filtered, washed, and vacuum dried for 2 hours to obtain modified glass fibers.